Bioengineering of functional human induced pluripotent stem cell-derived intestinal grafts - Kentaro Kitano (Nature Portfolio, 2017)
There is a need for humanised grafts to treat patients with intestinal failure. Here, the authors generate intestinal grafts by recellularizing native intestinal matrix with human induced pluripotent stem cell-derived epithelium and human endothelium, and show nutrient absorption after transplantation in rats.